OPTIMIZATION OF OVERBURDEN DISTRIBUTION USING LINEAR PROGRAMMING AT GRASBERG OPEN PIT - MAHAYASA (NIM : 29107134); Pembimbing: Ir. Rudy Bekti, MM, MADE
Grasberg open pit one of the biggest copper and gold deposit in the world that is operated by PT Freeport Indonesia in district Mimika province of Papua. The rock type and the structure of this mine is very complex as the result of the deposit forming that was complex too. As the open pit, Grasberg produces ore and overburden. The ore will be mined and hauled to Mill after crushed by crusher and transported using belt conveyor. The overburden will be dug and hauled to dump area. Grasberg pit has 21 rock type of overburden. These rock can not be dumped to all dump area because they have different criteria and accept specific rock type only. The Long Range Planning do the forecast each quarter including mine and dump plan. One of the task during forecasting is distributing overburden from each phase to each dump for each period (monthly, quaterly, and yearly) matching with the dump criteria and priority. This job was done manually for monthly plan of the current year and get help from Minesight Strategic Planner (MSP) for life of mine. MSP distribute the overburden based on the shortest path. This final project will review the benefit of using linear programming in the overburden distribution for long range planning. Using the same parameter, the result of this optimization is compared to the current system. The result shows the benefit of using linear programming is increasing the NPV by US $ 30.1 millions for life of mine in year 2009 Ã‚Â– 2015. The implementation of linear programming in the overburden distribution need some preparations and take about one month. The cost of software is low as compared to the benefit. Therefore this system will help optimizing the overburden distribution to get lower operating cost and this system will reduce the load of mine engineer to do his task.